Relationship between the maxillary sinus and apices of posterior-superior teeth using cone beam computed tomography - Rodríguez, Macarena Cecilia; Richa, Roxana; Valenzuela, Juan Jose; Niklander Ebensperger, Sven. (Universidad de la Frontera, 2023)
Knowledge of the relationship between the maxillary sinus and the apices of the upper posterior teeth is crucial to avoid complications when considering different treatments. A descriptive cross-sectional study was carried out, with a convenience sample of 383 images of upper posterior teeth roots, obtained by means of cone beam computed tomography (CBCT) from a radiological center in Viña del Mar, Chile. Each root was classified according to its vertical relationship with the sinus into 4 categories (0: apex is not in contact with the lower contour of the sinus; 1: apex is in contact with the sinus; 2: apex laterally to the sinus; 3: apex protrudes in sinus). In addition, its distance was measured in mm. The data were analyzed with descriptive statistics. The tooth farthest from the maxillary sinus was the maxillary first premolar (4.2 mm), followed by the maxillary second premolar (1 mm). In the upper first molar, the most distant root was the mesiobuccal (MV) 1mm, followed by the distobuccal root (DV) 0.6mm and the palatal root (P)-1mm. In the upper second molar, the furthest root was P 0.4mm, then DV 0.3mm, and MV-0.11mm. In reference to the categories, it was observed that most of the roots are far from the sinus, with the P root of the first upper molar and the MV root of the second upper molar being the most protruding (42 % and 26 % respectively). The first premolar is the posterior maxillary tooth that is furthest from the maxillary sinus and as one advances posteriorly there is a tendency to decrease the distance between the apices and the maxillary sinus.
Relación entre el seno maxilar y ápices de dientes postero-superiores con tomografía computarizada de haz cónico
Keywords: Seno maxilar; TCHC; Anatomía